Beyond perception of convenience: Exploring student use of food delivery services - Barcelona, Jersey Kirsten; Ragos, Marie Jo Tess; Libunao, Vhon Ivan; Misa, Mary Ann; Cynic, Cynic (Universitas Pendidikan Nasional, 2024)
This research investigated the underlying issues influencing students' use of food delivery services beyond the established convenience factor. The study utilized a qualitative approach, employing thematic analysis to gain a deeper understanding of how first-year students at the Technological University of the Philippines-Manila perceived food delivery services. A total of twelve (12) first-year Bachelor of Science in Food Technology (BSFT) students were chosen based on their experience with food delivery apps, willingness to participate, and the range of perspectives they offered. Semi-structured interviews were conducted using a pre-designed interview guide. The interview guide consisted of eleven (11) open-ended questions designed to explore aspects related to student perceptions of food delivery services. The findings revealed that food delivery apps had become an integral part of the students' daily lives. The convenience, speed, and variety offered by these apps were the primary drivers of their popularity among the respondents. While experiences with these services were generally positive, characterized by user-friendly interfaces and timely deliveries, certain areas required improvement. Notably, occasional issues such as late deliveries, high transaction fees, cold food, and unusable vouchers highlighted the need for enhanced service reliability and transparency. Additionally, cost-effectiveness remained a major concern, with students seeking budget-friendly options. This study advanced the understanding of the role of food delivery services in shaping the lifestyles and consumption behaviors of contemporary university students at the Technological University of the Philippines (TUP).